KRAS gene mutation in patients with primary colorectal cancer - Vu Thi, Minh Thuc; Le, Van Thieu; Huynh, Quang Huy; Nguyen, Minh Duc (Acta Medica, 2019)
Objective: KRAS mutation occurs in 30% to 50% of colorectal cancers. The aim of our study was to determine the frequency of KRAS mutations among patients with colorectal cancer; and the relationship with clinicopathologic features. Materials and Methods: 79 colorectal cancer cases at a hospital in Hai Phong of Vietnam were collected, including 45 colon cancer and 34 rectal cancer during January 2010 and July 2012. PCR amplification and DNA sequencing were used to detect mutations in exon 2 of KRAS gene. The study was based on informed consent and approval by the Ethics Committee of Viet Tiep Hospital. Results: KRAS mutation was found in 40.4% (225/557) colorectal cancer. All mutation locations were in codon 12. There was significant association (p < 0.05) between KRAS mutations, tumor size and tumor stage. No significant association was observed between KRAS mutations and gender, tumor location, tumor grade or histologic presence of mucin (p>0.05). Conclusion: Determining the KRAS mutational status of tumor samples has become an essential tool for managing patients with colorectal cancers Keywords: colorectal cancer, KRAS gene mutation, clinicopathology.